Increased cardiac myosin super-relaxation as an energy saving mechanism in hibernating grizzly bears - Robbert J. Van der Pijl; Weikang Ma; Christopher T.A. Lewis; Line Haar; Amalie Buhl; Gerrie P. Farman; Marcus Rhodehamel; Vivek P. Jani; O Lynne Nelson; Chengxin Zhang; Henk Granzier; Julien Ochala (Molecular Metabolism)
Aim: The aim of the present study was to define whether cardiac myosin contributes to energy conservation in the heart of hibernating mammals. Methods: Thin cardiac strips were isolated from the left ventricles of active and hibernating grizzly bears; and subjected to loaded Mant-ATP chase assays, X-ray diffraction and proteomics. Main findings: Hibernating grizzly bears displayed an unusually high proportion of ATP-conserving super-relaxed cardiac myosin molecules that are likely due to altered levels of phosphorylation and rod region stability. Conclusions: Cardiac myosin depresses the heart's energetic demand during hibernation by modulating its function.